Enhancement of Wind Energy Penetration Levels in Rural Grid Using ADALINE-LMS Controlled Distribution Static Compensator - Chawda, Gajendra Singh; Shaik, Abdul Gafoor (IEEE transactions on sustainable energy, 2022)
Wind Energy (WE) penetration levels in rural grids are limited due to the Power Quality (PQ) issues owing to the inconsistency in the wind speed and low short circuit ratios. This is further aggravated due to the day-by-day increase in non-linear loads. This paper proposes a methodology to enhance WE penetration levels by mitigating PQ issues using distribution static compensator (DSTATCOM) controlled by the Adaptive Linear Element-Least Mean Square (ADALINE-LMS) algorithm. The proposed adaptive control algorithm estimates the active and reactive weight components of load currents by considering the changes in wind generation, DC-link voltage and grid voltage. These weights are used to generate reference current signals to switch the DSTATCOM to mitigate PQ disturbances. The proposed method has been implemented for the enhancement of WE penetration in the rural grid under the non-linear load. The results obtained by simulation in MATLAB studies have been validated using the experimental studies. These studies established the effectiveness of the proposed method for enhancing WE penetration level in rural grid up to 25%.